RANCANG BANGUN PEMBELAJARAN BERBASIS WEBSITE UNTUK SISWA SEKOLAH DASAR - Pratista, Loveineza Florinadia Putri; Maslihah (Jurnal Multidisipliner Kapalamada, 2025)
This study designs and develops a web-based learning system for elementary school students using the Waterfall method. The system is developed as a digital solution to support teaching and learning activities more effectively. The main features include user data management (admin, teachers, students), material management, assignments, quizzes, automatic grading, as well as score and attendance recaps. The system interface is designed to be simple, interactive, and user-friendly so that it is easy for students to understand. Functionality testing was carried out using the black-box method involving teachers and students as users. The test results show that all features run according to requirements. The system not only provides an online learning platform but also serves as a tool to monitor students’ academic progress in real-time through a dashboard of grades and attendance. Thus, the system can assist schools in delivering learning that is more structured, flexible, and efficient.